ICE Relevant Physical-chemical Properties and Air Pollutant Emission of Renewable Transport Fuels from Different Generations – An Overview - Szabados, György; Knaup, Jan; Bereczky, Ákos (Periodica Polytechnica Transportation Engineering, 2022)
The fuel demand in transport sector seems to be raised on a short and also on a long term base in the European Union and worldwide as well. A constantly growing trend is foreseen through 2050 worldwide as for using bio-based energy or fuels. Questions can arise before using these kinds of fuels in connection with the use of clean water or in terms of soil degradation, plant nutrients. It is also questionable whether they can be useful regarding their usage. First-, and second generation liquid as well as third generation gaseous bio-based fuels will be in focus in this article. They will be analyzed from physical-chemical properties and pollutant emission points of view.